TURKEY’S FOREIGN TRADE AS A DRIVER OF ECONOMIC DEVELOPMENT - Masumova, N. R. (Vestnik MGIMO-Universiteta, 2016)
Turkey now is a regional leader due to economic success story of the past decade, changes in the economy's structure and dynamic. Since 1980th foreign trade has become the main driver of the economic growth. Due to liberalization policy Turkey was able to overcome the system crisis. The negative economic trends had contributed to the political instability. That's why it will be interesting to highlight some aspects of Turkish foreign trade policy, which influence the value, geographical and product orientation of foreign trade. Negative balance of trade is the result of its oil import dependence. But the export of goods with more value added has the trend to growth - 30% of exports come to machineries and transport equipments. After the collapse of the USSR Turkish-Russian economic relationship was facing revival. Trade and investment cooperation was developing rapidly. But the conflict of interest during the war in Syria led to growing differences between Russia and Turkey. 24th of November 2015 became a turning point for the Russian-Turkish relations, when Turkish fighter jet F-16 shot down a Russian military jet along the Syrian border. This tragedy had serious consequences for the bilateral economic relations. Huge investment pipeline project "Turkish stream" is freezed, the work of intergovernmental authorities is stopped, certain agricultural goods originated from Turkey is banned to the territory of the Russian Federation. Russia also suspended the visa-free regime for Turkish citizens, all charter flights to Turkey are prohibited. Nevertheless economic sanctions inevitable affect both the Turkish and Russian economies, but Russia is still one of the main partners of Turkey.